Morphometric study of the postnatal growth of the parotid gland of the mouse Estudo morfométrico do crescimento pós-natal da glândula parótida do camundongo - Tiago Turri de Castro Ribeiro; André Dotto Sottovia; Tania Mary Cestari; Rumio Taga (Sociedade Brasileira de Pesquisa Odontológica, 2006)
The growth of the mouse parotid glands during 7 and 35 days of postnatal life was studied by morphometric methods. The mass of the gland, the volume of each morphological compartment, and the cell number in each compartment were evaluated. The data obtained for each evaluated dimension were adjusted by an exponential equation, of the type Y = a.e k.x, thus permitting the calculation of their mean duplication time (T D), i.e., an estimation of their growth rate. Analysis of the results showed a marked 1,424% increase in the gland mass during the whole studied period, with T D = 7.10 days. This growth occurred by increases in absolute volume of acini, intercalated ducts, striated ducts, excretory ducts and stroma, with percentual increases of 3,048%, 417%, 2,662%, 2,594% and 367%, respectively, and T Ds of 5.62, 11.71, 5.55, 5.47 and 14.45 days, respectively. Analysis of the cell number growth in each compartment showed increases of 1,904%, 285%, 1,228%, 1,090% and 286%, respectively, and T Ds of 6.62, 20.40, 7.19, 7.26 and 14.51 days, respectively. Based on the present results, we concluded that the growth of the mouse parotid glands from day 7 to day 35 of age occurred by intense cell accumulation, mainly in the acini, striated ducts and excretory ducts, with a growth rate sensibly higher than that of the intercalated ducts and stroma. O crescimento das glândulas parótidas do camundongo durante 7 e 35 dias de vida pós-natal foi estudado por métodos morfométricos. A massa glandular, o volume de cada compartimento morfológico e o número de células em cada compartimento foram avaliados. Os dados obtidos para cada dimensão avaliada foram ajustados por equação exponencial, tipo Y = a.e k.x, permitindo o cálculo do seu tempo de duplicação médio (T D), ou seja, uma estimativa da sua velocidade de crescimento. A análise dos resultados mostrou a ocorrência de um marcante aumento de massa glandular no período estudado de 1.424%, com T D = 7,10 dias. Esse crescimento glandular ocorreu por aumentos nos volumes absolutos dos ácinos, dos ductos intercalares, dos ductos estriados, dos ductos excretores e do estroma, com aumentos percentuais de, respectivamente, 3.048%, 417%, 2.662%, 2.594% e 367%, e T Ds de 5,62, 11,71, 5,55, 5,47 e 14,45 dias. A análise da evolução do número de células em cada compartimento demonstrou aumentos de, respectivamente, 1.904%, 285%, 1.228%, 1.090% e 286% e T Ds de 6,62, 20,40, 7,19, 7,26 e 14,51 dias. Baseados nos resultados aqui obtidos, concluímos que o crescimento das glândulas parótidas do camundongo entre os dias 7 e 35 de idade ocorre por intenso acúmulo de células, principalmente nos ácinos e nos ductos estriados e excretores, com uma velocidade de crescimento sensivelmente maior que nos ductos intercalares e no estroma.